Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) dan Profil Pelajar Rahmatan Lil Alamin (P2RA) pada Siswa MI : Sebuah Upaya Membangun Karakter Disiplin dan Bertanggung Jawab Pada Siswa - Fauziah, Giska Enny; Rohmawati, Aulia (IBTIDA', 2023)
The implementation of the Pancasila Student Profile (P5) and Rahmatan Lil Alamin Student Profile (P2RA) projects for MI students is one of the efforts to build student character. The projects are expected to provide opportunities for students to learn and develop positive characters that are needed to be good citizens, especially discipline and responsibility. This study aims to examine the effectiveness of the implementation of the P5-P2RA projects in building the disciplined character and responsible character of MI students. This study uses a qualitative method with a literature study approach. Data were collected through observation and study kinds of literature. The results of the study show that the P5-P2RA projects have the potential to build the disciplined character and responsible character of MI students. The projects can provide opportunities for students to learn about the values of Pancasila and rahmatan lil alamin, and apply those values in their daily lives. Based on the results of this study, the P5-P2RA projects can be developed and optimized for the dicipline character and responsible character of MI students. This is important in order to have a greater impact on building the character of MI students. This is demonstrated through various activities that students can participate in with a sense of discipline and responsibility.